Finnish farmers’ climate change perceptions: Towards a psychological understanding of pro-environmental behavior in agriculture : Doctoral Dissertation - Sorvali, Jaana (Natural Resources Institute Finland (Luke), 2023)
Climate change is a global challenge, and solving it requires the combined effort of every nation and sector of life. The land-use sector is a significant source of greenhouse gas emissions but also an important carbon sink. The agricultural sector is obliged to mitigate emissions under the Paris Agreement, thus speeding up the research, policy development, and implementation of mitigation options. In agriculture, farmers’ decision making at the farm level is crucial for climate change mitigation and adaptation implementation, which underlines the importance of farmers’ perceptions of climate change. The scientific evidence for climate change is strong, but it has not resulted in public understanding and corresponding action to mitigate climate change. Physical, psychological, and social factors have been suggested as reasons for this imbalance of knowledge and action. As environmental psychology studies the interplay between individuals and the built and natural environment, it can facilitate the rectification of this imbalance through an understanding of the human behavior relevant for climate change, informing responses to climate change and understanding of peoples’ thoughts and feelings about climate change that in turn influence their motivations and pro-environmental behavior. Although farmers’ climate change perceptions are already well known, psychological research into this issue remains quite rare. This thesis will extend the theoretical perspective of environmental psychology to agricultural research. Two social psychological theories, the value-belief-norm (VBN) theory by Stern and the theory of basic human values by Schwartz et al. are used to study Finnish farmers’ pro-environmental behavior. A new psychological element of the climate change opportunity is also introduced, and its effects on pro-environmental behavior are discussed. This research is based on two surveys of the Finnish farmer population in 2018 and 2020. Altogether, 4,401 farmers responded to the 2018 survey, with a response rate of 12%. The follow-up survey in 2020 received 2,000 responses, a response rate of 45%. The sample represented the Finnish farmer population quite well in many different demographic and farm-specific aspects for both surveys. Statistical methods were used to analyze the data. The results of this thesis show that farmers have differing values and perceptions concerning climate change, and they perceive the connected risks and opportunities differently. This understanding is needed by agricultural policy planners and decision makers to draft policy measures that will be accepted and thoroughly implemented by farmers. Finnish farmers have a very high awareness of climate change, a strong notion that action must be taken, and that their actions will have an effect. The literature on agriculture and climate change has focused mainly on climate change risks and adaptation challenges and options, and less attention has been paid to mitigation or climate change opportunities. Globally, this is very understandable, as climate change risks are already experienced, and quick responses must be made on how to handle those risks. Moreover, discussing the opportunities of such a detrimental phenomenon as climate change can be seen as ethically unjust. Yet the results of this thesis highlight that opportunities are perceived by farmers, and that farmers feel confused because they are expected to simultaneously mitigate climate change and adapt to and benefit from the positive implications of climate change. Farmers are crucial in climate change mitigation in agriculture, as they are the ones making decisions at the farm level. Farmers’ felt possibility to mitigate climate change proved the most important predictor of pro-environmental behavior. Agricultural research and policy should therefore enable the adoption of tangible farm-specific climate change mitigation practices with undeniable environmental benefits that will increase farmers’ motivation to mitigate climate change.
Keywords: farmer; agriculture; climate change; psychology; behavior